2014
DOI: 10.1371/journal.pgen.1004783
|View full text |Cite
|
Sign up to set email alerts
|

HAM-5 Functions As a MAP Kinase Scaffold during Cell Fusion in Neurospora crassa

Abstract: Cell fusion in genetically identical Neurospora crassa germlings and in hyphae is a highly regulated process involving the activation of a conserved MAP kinase cascade that includes NRC-1, MEK-2 and MAK-2. During chemotrophic growth in germlings, the MAP kinase cascade members localize to conidial anastomosis tube (CAT) tips every ∼8 minutes, perfectly out of phase with another protein that is recruited to the tip: SOFT, a recently identified scaffold for the MAK-1 MAP kinase pathway in Sordaria macrospora. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
135
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(149 citation statements)
references
References 77 publications
(123 reference statements)
12
135
0
1
Order By: Relevance
“…However, oscillation, chemotropic interactions, and fusion were never observed in the Dham-5; his-3:: ham-5 1-523 -gfp strains. Nuclear localization was also observed for HAM-5 1-351 -GFP that contained the seven WD40 repeats ( Figure 1E, WD40) (Jonkers et al 2014), but no cytoplasmic puncta were observed. Thus, the domain required for nuclear exclusion of HAM-5 is situated between amino acids 523 and 777 and sequences important for localization of HAM-5 to puncta are between amino acids 351 and 523.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…However, oscillation, chemotropic interactions, and fusion were never observed in the Dham-5; his-3:: ham-5 1-523 -gfp strains. Nuclear localization was also observed for HAM-5 1-351 -GFP that contained the seven WD40 repeats ( Figure 1E, WD40) (Jonkers et al 2014), but no cytoplasmic puncta were observed. Thus, the domain required for nuclear exclusion of HAM-5 is situated between amino acids 523 and 777 and sequences important for localization of HAM-5 to puncta are between amino acids 351 and 523.…”
mentioning
confidence: 77%
“…In the filamentous ascomycete fungus, Neurospora crassa, genetically identical germinated asexual spores (germlings) undergo fusion to form a syncytium that is an interconnected network of fused cells Leeder et al 2013;Herzog et al 2015). An important pathway required for both germling and hyphal fusion is a conserved mitogen-activated protein kinase (MAPK) cascade that includes the MAPK kinase kinase NRC-1, the MAPK kinase MEK-2, the MAPK MAK-2, and the scaffold protein, HAM-5 (Pandey et al 2004;Dettmann et al 2012Dettmann et al , 2014Jonkers et al 2014). During germling fusion, chemotrophic growth is associated with oscillation of the MAK-2/MEK-2/NRC-1/HAM-5 complex and the regulatory adaptor subunit STE-50 to the fusion tips of germlings, conidial anastomosis tubes (CATs), and to the tips of hyphae undergoing chemotropic interactions prior to cell fusion (fusion hyphae) (Fleissner et al 2009;Dettmann et al 2012Dettmann et al , 2014Jonkers et al 2014 signaling complex is perfectly out of phase with a second protein, called SOFT, which is also essential for chemotropic interactions and cell fusion (Fleissner et al 2005).…”
mentioning
confidence: 99%
See 3 more Smart Citations